2021
DOI: 10.1186/s12998-021-00408-y
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injection or dry needling for musculoskeletal pain and disability? A systematic review and GRADE evidence synthesis

Abstract: Background Corticosteroid injection and dry needling have been used in the treatment of musculoskeletal conditions, but it is unclear which intervention is the most effective. The purpose of this study was to compare the effects of corticosteroid injection and dry needling for musculoskeletal conditions at short-, medium-, and long-term follow-up. Methods Electronic databases were searched up to 31 October 2021. Two researchers independently screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Another myofascial trigger point DN study in knee OA 31 revealed that both the trigger point DN and standard acupuncture groups experienced significant improvements in pain and function; however, trigger point therapy may be more beneficial. Sousa Filho et al, 12 in their recent meta-analysis, examined DN versus corticosteroid injections for musculoskeletal pain and disability. Their analysis of six RCTs (384 patients) showed that corticosteroid was more effective than DN for plantar fasciitis and lateral epicondylitis in the short and midterm but less effective in the long-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another myofascial trigger point DN study in knee OA 31 revealed that both the trigger point DN and standard acupuncture groups experienced significant improvements in pain and function; however, trigger point therapy may be more beneficial. Sousa Filho et al, 12 in their recent meta-analysis, examined DN versus corticosteroid injections for musculoskeletal pain and disability. Their analysis of six RCTs (384 patients) showed that corticosteroid was more effective than DN for plantar fasciitis and lateral epicondylitis in the short and midterm but less effective in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…7 9 Trigger points commonly emerge in conditions like OA. 10 The mechanism of DN is not completely understood; however, its efficacy and effectiveness have been studied in the management of various musculoskeletal pain syndromes 9,11,12 in regions like the knee, 13,14 lower extremity, 8 plantar region, 15 low back, 16 elbow, 17 shoulder 18,19 and neck. 20 To our knowledge, only one systematic review has examined the effect of DN on hip disease.…”
Section: Introductionmentioning
confidence: 99%
“…[6] A recent systematic review suggests that acupuncture can reduce PHPS pain in the short term, however, more nuanced issues, such as how practitioners choose different acupuncture in different situations, remain unclear. [7] Previous studies have reported electroacupuncture for analgesia. [8,9] Warm needling therapy is an indirect moxibustion method that can be combined with acupuncture.…”
Section: Openmentioning
confidence: 99%
“…[ 6 ] A recent systematic review suggests that acupuncture can reduce PHPS pain in the short term, however, more nuanced issues, such as how practitioners choose different acupuncture in different situations, remain unclear. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation